Diari 1952-1962 - Dessì, Giuseppe (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2011)
In these private notes, the quest for the self appears like a journey of dual metaphorical significance through the intricate weft of the pages and the labyrinth of life. The Diari 1952-1962 of Giuseppe Dessí are presented here in Franca Linari's meticulous transcription accompanied by an introduction and an attentive commentary by Francesca Nencioni. Following the previous volumes, which made it possible to reconstruct the history of his youthful education and the productions of his early maturity, this one now reveals significant changes in the writer's life. A new female figure (Luisa) accompanies a period in which the narrative production that has become the dominant passion becomes decidedly more intensive and continuative, hand-in-hand with an increase in the collaborations with journals and the desire to experiment new forms of expression ushered in by the theatre.